2017
DOI: 10.2147/tcrm.s129327
|View full text |Cite
|
Sign up to set email alerts
|

Genetic factors in pathogenesis of diabetes mellitus after kidney transplantation

Abstract: Posttransplant diabetes mellitus (PTDM) is one of the major metabolic complications after transplantation of solid organs including the kidney. This type of diabetes mellitus affects allograft survival, cardiovascular complications and overall patient survival. The modifiable risk factors that contribute to PTDM include obesity, some viral infections (eg, hepatitis C virus, cytomegalovirus) and especially immunosuppressive drugs including corticosteroids, tacrolimus, cyclosporine and sirolimus. Currently, pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 78 publications
(85 reference statements)
2
11
0
Order By: Relevance
“…Associations of IL6 GG, IL-4 CC, IFNG TT and TGFB TT genotypes were superseded by age group and bio-physiology of patients. This might confirm identified differences in innate immune system in older KTRs compared to younger ones 65 .…”
Section: Discussionsupporting
confidence: 71%
“…Associations of IL6 GG, IL-4 CC, IFNG TT and TGFB TT genotypes were superseded by age group and bio-physiology of patients. This might confirm identified differences in innate immune system in older KTRs compared to younger ones 65 .…”
Section: Discussionsupporting
confidence: 71%
“…We examined the incidence of and risk factors for PTDM after kidney transplantation in Taiwanese patients, and there have been few such studies in the past. At 1, 3, and 5 years after transplantation, the proportion of patients who developed PTDM (Table 2) was not similar to that reported in previous studies (e.g., 13.00% (American study) and 11.80% (Korean study) after 1 year, 30.72% after 3 years (Chinese study), and 15.10% after 5 years (Japanese study)) [2,10,16,17]. The incidence rate of PTDM in both the American and Korean studies was higher than that reported here; this could be attributed to the relatively higher BMI in the American study (27 ± 5 kg/m 2 ) or the inclusion of patients with temporary hyperglycemia resulting from the consumption of high doses of corticosteroids to prevent acute rejection in the Korean study [2,16].…”
Section: Incidence Of Ptdmmentioning
confidence: 46%
“…However, risk factors for PTDM differ from those associated with type 2 diabetes. The common risk factors for PTDM include obesity, sedentary lifestyle, other metabolic syndromes associated with obesity, certain viral infections (e.g., hepatitis C virus and cytomegalovirus), and the use of drugs with diabetogenic effects administered with post-transplantation therapy, including corticosteroids and immunosuppressive agents (e.g., tacrolimus, cyclosporine, and mammalian target of rapamycin inhibitors (mTORis)) [13]. Other immunosuppressive drugs, including azathioprine and mycophenolate mofetil (MMF), are not associated with a disruption in glucose metabolism [14].…”
Section: Introductionmentioning
confidence: 99%
“…Other groups of genes assessed in their relation to PTDM are interleukins (ILs) and inflammation-related factors. Inflammatory chemokines and cytokines have been shown to be involved in peripheral insulin action and insulin secretion [ 78 ]. ILs and other molecules secreted by T cells mediate inflammation via the promotion of the production of inflammatory cytokines (TNF-α, IL-1B, and IL-6) [ 78 ].…”
Section: Prediabetes and Post-transplant Diabetes Mellitus (Ptdm)—mentioning
confidence: 99%
“…Inflammatory chemokines and cytokines have been shown to be involved in peripheral insulin action and insulin secretion [ 78 ]. ILs and other molecules secreted by T cells mediate inflammation via the promotion of the production of inflammatory cytokines (TNF-α, IL-1B, and IL-6) [ 78 ]. G allele at position 2174 of the IL-6 gene promoter has been shown to be associated with the risk of PTDM among overweight subjects [ 79 ].…”
Section: Prediabetes and Post-transplant Diabetes Mellitus (Ptdm)—mentioning
confidence: 99%